2002
DOI: 10.1046/j.1365-294x.2002.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation in Pleistocene and modern Atlantic salmon from the Iberian glacial refugium

Abstract: Current understanding of the postglacial colonization of Nearctic and Palearctic species relies heavily on inferences drawn from the phylogeographic analysis of contemporary generic variants. Modern postglacial populations are supposed to be representative of their Pleistocene ancestors, and their current distribution is assumed to reflect the different colonization success and dispersal patterns of refugial lineages. Yet, testing of phylogeographic models against ancestral genomes from glacial refugia has rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
132
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 65 publications
(117 reference statements)
6
132
0
Order By: Relevance
“…In agreement with this climatic history, the majority of the studies found evidence of Pleistocene bottlenecks that were likely caused by periods of strong ocean cooling (e.g. Consuegra et al 2002;Domingues et al 2006Domingues et al , 2007bDomingues et al , 2008Mäkinen and Merilä 2008). However, populations of diVerent species vary in their phylogeographic patterns and we are still far from a comprehensive picture of the evolution of the western European marine icthyofauna during the Pleistocene.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…In agreement with this climatic history, the majority of the studies found evidence of Pleistocene bottlenecks that were likely caused by periods of strong ocean cooling (e.g. Consuegra et al 2002;Domingues et al 2006Domingues et al , 2007bDomingues et al , 2008Mäkinen and Merilä 2008). However, populations of diVerent species vary in their phylogeographic patterns and we are still far from a comprehensive picture of the evolution of the western European marine icthyofauna during the Pleistocene.…”
Section: Introductionmentioning
confidence: 66%
“…For the other locations, the spatial expansion model also Wtted the data although the sudden expansion model could not be rejected. The Iberian Peninsula constituted an important glacial refugium for the Atlantic salmon Salmo salar (Consuegra et al 2002). These authors, using ancient salmon DNA, provided evidence suggesting that the present-day genetic make-up of the salmon populations of northern Spain diVers from their constitution during the last glaciation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual genetic structure in the Baltic Sea may have resulted from population isolation during the complex marine transgression history resulting from the interplay of sea level changes and the isostatic rebound in the early Quaternary (Lepiksaar, 2001, p. 40). However, it has also been used to infer recolonization from possible glacial refugia in the southern North Sea or beyond the eastern edge of the Fennoscandian ice sheet (e.g., Consuegra et al, 2002;Langefors, 2005;King et al, 2007; but see also Makhrov et al, 2005). A westward recolonization pathway into the Baltic Sea from the White Sea after the LGM was previously perceived as unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the Atlantic salmon is one of the few species where MH polymorphism has been experimentally shown to be associated with resistance/susceptibility to specific pathogens (Grimholt et al, 2003). Furthermore, historical samples are widely available from Atlantic salmon populations, often as dried scales that are suitable for extraction of DNA, allowing analysis of temporal variation within populations (Nielsen et al, 1999;Consuegra et al, 2002;Ciborowski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%